Peran tri pusat pendidikan dalam membentuk karakter disiplin siswa kelas III SD Negeri Bangunharjo - Ruwaidha, Nitis Oka; Trisharsiwi, Trisharsiwi (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2024)
This study aims to describe the role of the Tri Education Center in shaping the disciplinary character of grade III students at SD Negeri Bangunharjo and describe the efforts made in forming the character of the discipline. Conducted from October 2022 to January 2023, the study involved 2 grade III students at SD Negeri Bangunharjo with subjects including principals, teachers, parents, and peers. The data collection method uses interviews, observation, and documentation, with data validity tested through triangulation. Data analysis follows Miles and Huberman's approach, including collection, reduction, presentation, and inference. The results showed the important role of parents as role models in shaping disciplinary character, schools as educational institutions that provide character education, and the community environment as an example of integrity and tolerance. Efforts to build disciplinary character involve planning by making rules of conduct, implementation through examples of attitudes and behaviors, and evaluation by observing and reviewing regulations. Overall, this study provides a holistic picture of the role and efforts made by the Tri Education Center in shaping the disciplinary character of grade III students at SD Negeri Bangunharjo.